Reporter‐based forward genetic screen to identify bundle sheath anatomy mutants in A. thaliana. (18th January 2019) - Döring, Florian; Billakurthi, Kumari; Gowik, Udo; Sultmanis, Stefanie; Khoshravesh, Roxana; Das Gupta, Shipan; Sage, Tammy L.; Westhoff, Peter
Summary: The evolution of C4 photosynthesis proceeded stepwise with each small step increasing the fitness of the plant. An important pre‐condition for the introduction of a functional C4 cycle is the photosynthetic activation of the C3 bundle sheath by increasing its volume and organelle number. Therefore, to engineer C4 photosynthesis into existing C3 crops, information about genes that control the bundle sheath cell size and organelle content is needed. However, very little information is known about the genes that could be manipulated to create a more C4 –like bundle sheath. To this end, an ethylmethanesulfonate (EMS)‐based forward genetic screen was established in the Brassicaceae C3  species Arabidopsis thaliana . To ensure a high‐throughput primary screen, the bundle sheath cells of A. thaliana were labeled using a luciferase (LUC68) or by a chloroplast‐targeted green fluorescent protein (sGFP) reporter using a bundle sheath specific promoter. The signal strengths of the reporter genes were used as a proxy to search for mutants with altered bundle sheath anatomy. Here, we show that our genetic screen predominantly identified mutants that were primarily affected in the architecture of the vascular bundle, and led to an increase in bundle sheath volume. By using a mapping‐by‐sequencing approach the genomic segments that contained mutated candidate genes were identified. Significance statement: We present a robust method using Arabidopsis thaliana as a model system to efficiently induce mutations that affect bundle sheath anatomy using ethyl methanesulfonate and to map the responsible genomic region by mapping by sequencing. The key feature of this method is the use of easily detectable reporter genes for the primary screening of mutant candidates. We believe that this method is generally applicable for creating mutants that are affected in inner leaf anatomy.